Fenomena Flexing Di Medsos : Dampaknya Pada Hubungan Sosial dan Ekonomi: The Phenomenon Of Flexing On Social Media: Its Impact On Social And Economic Relations - Nur Wahidah, Jumaiyah; Khodijah, Khodijah (Hidmah : Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
The flexing phenomenon on social media can increase a person's popularity in forming a self-image. Social media has developed into an important platform for developing their reputation and popularity in the modern digital era. The practice of "flexing," defined as flaunting wealth, luxurious lifestyles and accomplishments on social media. The method used is qualitative using a phenomonological approach and is descriptive because the researcher aims to obtain an in-depth picture regarding the flexing phenomenon which is currently being widely discussed by the public. The description in question is that the researcher describes various situations, conditions and various variables. The results and discussion of the research are that the flexing phenomenon should be avoided because it gives rise to a cheerful or ostentatious nature. Playfulness is not recommended for Muslims because it has a negative impact on themselves and others. And it also has a negative impact on social and economic relations where someone is more concerned with appearance than reality and this action can increase consumption and encourage each individual to spend unnecessarily.